Creating Model with System Breakdown Structure for System Dynamics - Feldiansyah Bin Bakri Nasution; Nor Erne Nazira Bazin (Institute of Advanced Engineering and Science, 2017)
A system is developed as a set of components and subsystems. A subsystem is a smaller system inside the main system and consists of its constituent components. The continual improvement process concept is adopted in System Dynamics’s model creation. New components or subsystems are identified in each cycle of the process. The interrelation between components could be changed as the time is running. The continual improvement process is an ongoing effort in identifying an ideal model. In this paper, the system is explained as the set theory for better understanding. It is emphasized that by breaking down the system into smaller entity such as components and subsystems will make the analytics process more systematic and scalable. It is called as System Breakdown Structure (SBS). At the end of this paper, the model before and after SBS are evaluated by comparing the output and the state of system.